The Visual Psychological Influence of Cadet Soldiers on Terracotta Materials on the Shape of the Facade of the Main Hall Building of Akmil Magelang - Hermanto, Bambang; Eni, Sri Pare; Pasaribu, Ramos P. (Jurnal Indonesia Sosial Sains, 2025)
The Indonesian Army Military Academy (Akmil) in Magelang, established on October 31, 1945, plays a key role in the education and development of career officers for the Indonesian Army (TNI AD). This research aims to evaluate the design of a new Main Hall facility at Akmil, focusing on the use of terracotta materials for its façade. This study employs a quantitative research method with a descriptive approach, supported by qualitative insights from interviews. The primary objective is to empirically assess the psychological impact of terracotta materials on the façade of the Main Hall at Akmil. Data collection involves questionnaires and surveys targeting cadet soldiers to assess their visual perceptions, emotional responses, and preferences regarding the terracotta façade. The proposed design using terracotta materials for the façade is anticipated to enhance both the physical and emotional appeal of the Main Hall. The use of terracotta is expected to create a welcoming, symbolic landmark that reinforces Akmil’s institutional identity and the pride of its personnel. The new Main Hall, incorporating terracotta, promises to address the space limitations while enhancing the psychological and symbolic value of the building. This upgrade will strengthen Akmil’s role as a leading institution in military education. The findings provide insights into how architectural design can contribute to both functional efficiency and emotional well-being in military institutions. This research offers recommendations for future military building designs, emphasizing the importance of material selection for promoting institutional pride and identity.